Discussing the Trend of Class Action in Consumer Dispute Settlement Based on the Lawsuit Against Apple over Slowing Down iPhones in Vietnam - Thuy, Phan Thi (VNU Journal of Science: Legal Studies, 2018)
On January 10, 2018, two Vietnamese lawyers representing a large number of consumers across the country instituted a civil case against Apple Inc. to the People's Court of Ho Chi Minh City for the reason that this corporation violated the manufacturer’s responsibility and caused damage to the users of iPhones in Vietnam. The lawsuit has been quickly paid attention to by legal practitioners, scholars and public opinion. This article analyzes and points out the legal challenges that the lawsuit posed to the court system and the indispensable trend toward class action lawsuit in the Vietnamese civil procedure law. Keywords Consumer, institute a civil case, class action, iPhone, Apple, Vietnam. References [1] Jordan Buie, Meet Mt. Juliet teen who showed how Apple slows down old iPhones on Reddit , USA TODAY NETWORK – Tennessee December 22, 2017 inhttps://www.tennessean.com/story/news/2017/12/22/mount-juliet-teens-iphone-discovery-goes-viral-leads-lawsuits-against-apple/976745001/ (truy cập 20/1/2018). [2] Apple Inc., A Message to Our Customers about iPhone Batteries and Performance , in https://www.apple.com/lae/iphone-battery-and-performance/ December 28,2017(truy cập 01/3/2018). [3] Yoni Heisler, There are now almost 60 class-action lawsuits against Apple for secretly throttling iPhones tại http://bgr.com/2018/02/26/iphone-battery-class-action-lawsuits-consolidation/ (updated 26 February 2018). [4] Văn phòng Luật sư Kết Nối, http://batterydown.vn/#vebatterydown (truy cập 17/3/2018). [5] Phan Thương, Người Việt kiện Hãng Apple, được không? Báo Thanh niên Điện tử sốra 04/3/2018 tại https://thanhnien.vn/thoi-su/nguoi-viet-kien-hang-apple-duoc-khong-938358.html(truy cập 19/3/2018). [6] Cục Canh tranh và Bảo vệ người tiêu dùng, Thông báo về vụ việc Apple Inc. làm chậm tốc độ các sản phẩm điện thoại Iphone thế hệ cũngày 20-01 2018, tạihttp://www.vca.gov.vn/chitietbvntd.aspx?ID=3859&Cate_ID=436(cập nhật 20/3/2018). [7] Quốc Chiến, Vụ kiện Apple làm chậm iPhone: Tòa án khất hẹn lần thứ 4 ,Báo Người Lao động điện tử, số ra 18/3/2018 tại https://nld.com.vn/phap-luat/vu-kien-apple-lam-cham-iphone-toa-an-khat-hen-lan-thu-4-20180318122905218.htm (truy cập 20/3/2018). [8] Hải Duyên, Tòa từ chối thụ lý vụ kiện Apple làm chậm iPhone , Báo điện tử VNExpress ngày 28/3/2018 tại https://vnexpress.net/tin-tuc/phap-luat/toa-tu-choi-thu-ly-vu-kien-apple-lam-cham-iphone-3729064.html (truy cập 28/3/2018). [9] Quốc Chiến, Tòa cần thêm thời gian xem xét vụ luật sư kiện Apple, Báo Người Lao động điện tử tại https://nld.com.vn/phap-luat/toa-can-them-thoi-gian-xem-xet-vu-luat-su-kien-apple-20180122194958179.htmngày 22/01/2018 (cập nhật 15/3/2018). [10] Becher, S.I., Asymmetric Information in Consumer Contracts: The Challenge that is Yet to be Met, American Business Law Journal, , 2008,. Vol. 45, tr.11-13. [11] Phan Thị Thanh Thủy, Kiện tập thể trong giải quyết tranh chấp tiêu dùng ở một số nước ASEAN và những gợi ý cho Việt Nam , Tạp chí Nhà nước và Pháp Luật,. 1(357)/2018, tr. 47-49.